Personal Branding Fadli Zon Studi pada Akun Twitter (Akun Twitter Fadli Zon @fadlizon sebagai Calon Legislatif) - Megayanti, Ni Luh Indah; Purnawan, Ni Luh Ramaswati; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2021)
- ABSTRACT- Personal branding of political actors is a step to shape people’s perception of aspects, including personality, ability, skills to integrity. The use of social media by political actors asaa medium of political communication is one of the steps in the formation of personal branding of legislative candidates. This study aims to analyze Fadli Zon’s personal branding as a legislative candidate on @fadlizon personal twitter account during the campaign period of 28 th September 2018 – 13 rd April 2019. This researchUuses qualitative descriptive research method and analyzed using three main dimensions of personal branding shaper. The result of this study was found 6 tweets without re-tweet found in the period 28 th September 2018 – 13 rd April 2019. During the campaign, Fadli Zon showed that he was critical, technologically responsive, credible, and populist legislative candidate. Keywords: personal branding, the main form of three dimensions of personal branding, tweet, legislative candidate.